MicroRNAs in Macrobrachium olfersii embryos: Identification, their biogenesis components and potential targets. (February 2019) - Jaramillo, Michael L.; Guzman, Frank; da Fonseca, Guilherme C.; Margis, Rogerio; Müller, Yara M.R.; Ammar, Dib; Nazari, Evelise M.
Graphical abstract: Highlights: Seven conserved and 10 novel miRNAs were identified in M. olfersii embryos. miRNA biogenesis components are evolutionarily conserved. In general, 516 miRNA targets were predicted in M. olfersii . Among the miRNAs identified, 10 novel miRNAs were Macrobrachium genus-specific. Abstract: In embryonic development, microRNAs (miRNAs) regulate the complex gene expression associated with the complexity of embryogenesis. Today, few studies have been conducted on the identification of miRNAs and components of miRNA biogenesis on embryonic development in crustaceans, especially in prawns. In this context, the aim of this study was to identify in silico components of miRNA biogenesis, and miRNAs and potential target genes during embryonic development in the prawn Macrobrachium olfersii through small RNAs and transcriptome analyses. Using the miRDeep2 program, we identified 17 miRNA precursors in M. olfersii, which seven (miR-9, miR-10, miR-92, miR-125, miR-305, miR-1175, and miR-2788) were reported in the miRBase database, indicating high evolutionary conservation of these sequences among animals. The other 10 miRNAs of M. olfersii were novel miRNAs and only similar to Macrobrachium niponnense miRNAs, indicating genus-specific miRNAs. In addition, eight key components of miRNA biogenesis (DROSHA, PASHA/DGCR8, XPO5, RAN, DICER, TRBP2, AGO, and PIWI) were identified in M. olfersii embryos unigenes. In the annotation of miRNA targets, 516 genes were similar to known sequences in the GenBank database. Regarding the conserved miRNAs, we verified that they were differentially expressed during embryonic development in M. olfersii . In conclusion, this is the first study that identifies conserved and novel miRNAs in the prawn M. olfersii with some miRNA target genes involved in embryonic development. Our results will allow further studies on the function of these miRNAs and miRNA biogenesis components during embryonic development in M. olfersii and other prawns of commercial interest.